1997
DOI: 10.1002/(sici)1097-0282(19970415)41:5<481::aid-bip1>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulated fluorescence depolarization due to energy transfer as tools to study DNA-dye interactions

Abstract: A method to study DNA‐dye complexes by the combination of steady state fluorescence anisotropy measurements and computer simulations of the fluorescence depolarization due to resonance energy transfer is presented. The simulations are based on a Markov chain analysis, assuming random distribution of the dyes along the DNA chain and energy transfer that obeys Förster kinetics. Since the investigated intercalators (ethidium bromide, YO, PO) and groove binders [4′6‐diamidino‐2‐phenylindole (DAPI)] were found to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…15 This angle was determined to be 51 • , 15 based on one bis-intercalating dye dimer sandwiched two base pairs and every chromophore unwinding the DNA helix by ∼20 • . 8,11,15,43 In the case of energy transfer between the chromophores, the emitted photon is equally likely emitted by either of the two. 15 Therefore, such energy transfer can be emulated in the simulations by setting β = 51 • /2 = 25 • as the effective azimuthal angle between the absorbing and emitting dipoles.…”
Section: Data Fitting and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…15 This angle was determined to be 51 • , 15 based on one bis-intercalating dye dimer sandwiched two base pairs and every chromophore unwinding the DNA helix by ∼20 • . 8,11,15,43 In the case of energy transfer between the chromophores, the emitted photon is equally likely emitted by either of the two. 15 Therefore, such energy transfer can be emulated in the simulations by setting β = 51 • /2 = 25 • as the effective azimuthal angle between the absorbing and emitting dipoles.…”
Section: Data Fitting and Analysismentioning
confidence: 99%
“…8,11,15,43 In the case of energy transfer between the chromophores, the emitted photon is equally likely emitted by either of the two. 15 Therefore, such energy transfer can be emulated in the simulations by setting β = 51 • /2 = 25 • as the effective azimuthal angle between the absorbing and emitting dipoles. In practice, the two chromophores of a YOYO dimer are indeed close enough such as to allow efficient transfer.…”
Section: Data Fitting and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation of Carlsson and co-workers show that DNA intercalated at 0.2 dye/bp caused depolarization 0.4. 11 Since the anisotropy data of the 1 kpb ladder samples at zero intercalation are unknown, the anisotropy calculations from Carlsson's model cannot be accomplished. Comparison with the data in Fig.…”
Section: Nucleic Acid Ce Separations With Polarized Fluorescence Detementioning
confidence: 99%
“…Other multiphoton fluorescence studies that have been reported relate directly to biological and other systems featuring both single center chromophores and energy trapping sites. [10][11][12][13][14][15][16][17][18][19][20] These, together with the well-known use of FRET as a spectroscopic ruler, [21][22][23][24][25] reflect the practical utility of the theory to be developed.…”
Section: Introductionmentioning
confidence: 99%